IMPLIKASI STRATEGI PEMASARAN MELALUI KOMODIFIKASI AGAMA DI INDONESIA - Yustati, Herlina (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2018)
Religion in Indonesia is divided into Muslim, Christian, Catholic, Hindu, Buddhist, Khong Hu Chu and Other Religions. Religion Islam is the majority religion embraced by the Indonesian population, so that business people use this opportunity to re-commodification of religion. Commodification describes how capitalism launched an aim to accumulate capital, or realize the transformation of use-value into exchange value. The commodification of Islam in Indonesia occurred in various aspects. Mislanya commodification